2017
DOI: 10.2135/cropsci2017.03.0182
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Germination and Emergence under High Diurnal Temperatures

Abstract: In tropical climates, high soil temperatures during the cotton (Gossypium hirsutum L.) planting season impair seed germination and plant emergence, resulting in poor stand establishment. Under these conditions, the performance of cultivars presently in use is not known. The aim of this study was to evaluate germination and emergence of cotton cultivars under diurnal high temperature cycles without water restriction. Three experiments were conducted in germination chambers, testing six cotton cultivars and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…All experimental materials were screened for germination ability at the minimum cardinal temperature of 15°C and at the critically low temperature of 12°C following a modified method by Raphael et al (2017). Briefly, 30 seeds of each of the GDRS accessions and FA mutants were surface-sterilized with 70% ethanol (v/v) for 1 min and with 20% bleach (v/v) for 10 min before rinsing them three times with sterile, distilled water.…”
Section: Cold Germination Screeningmentioning
confidence: 99%
“…All experimental materials were screened for germination ability at the minimum cardinal temperature of 15°C and at the critically low temperature of 12°C following a modified method by Raphael et al (2017). Briefly, 30 seeds of each of the GDRS accessions and FA mutants were surface-sterilized with 70% ethanol (v/v) for 1 min and with 20% bleach (v/v) for 10 min before rinsing them three times with sterile, distilled water.…”
Section: Cold Germination Screeningmentioning
confidence: 99%
“…Similarly, a study by Raphael et al. () indicated that larger seed mass improves performance at both sub‐ and supra‐optimal temperature conditions. Similar effects were observed in the present experiment, where a significant cultivar and planting date interaction was observed in both 2017 and 2018.…”
Section: Discussionmentioning
confidence: 80%
“…On comparing the effect of three selected planting dates on early season growth and seedling development, May plantings in 2017 and June plantings in 2018 resulted in significantly higher values for the measured vigor indicators when compared to the other two planting dates in the respective seasons (Figure 1). Similarly, a study by Raphael et al (2017) indicated that larger seed mass improves performance at both sub-and supra-optimal temperature conditions. Similar effects were observed in the In the present study it was hypothesized that both FTLA and A n will be positively associated with seedling vigor.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations